Bring Your Whole Self to Work: Boundary Conditions of Subjectivity in Diversity and Inclusion Discourse on Investment Bank Websites - Carr, Melissa (Journal of business ethics, 2026)
This article critically examines the discourse of ‘bring your whole self to work’ within the diversity, equality, and inclusion (DEI) narratives of investment banks. While inclusion is often framed as essential for leveraging diversity, scholars argue that ‘whole self’ approaches risk individualising diversity and reinforcing systemic exclusions. Drawing on Foucault’s concepts of biopower, technologies of the self, and governance, this study explores how inclusion operates as a mechanism of organisational power, shaping subjectivities through corporate DEI statements. Using discourse analysis of investment banks’ websites, the article identifies three subjectivities constructed through ‘whole self’ discourse: the whole self as a driver of productivity, the whole self shaped by wellness and mindset, and the whole self oriented towards personal growth. By interrogating the boundary conditions of inclusion, the article highlights the ethical implications of DEI discourse, questioning how organisations define acceptable identities and reinforcing the need for structurally inclusive practices that move beyond surface-level commitments.